Pengaruh Metode Pembelajaran dan Kecerdasan Sosial terhadap Hasil Belajar Pendidikan Kewarganegaraan - Fitriani - (JTP - Jurnal Teknologi Pendidikan, 2015)
This study aims to discover the correlation of learning methods and social intelligence of students' learning outcomes in citizenship course. The participants were 54 students were divided into two treatment classes. The results of study: (1) collaborative learning method is better rather than problem solving; (2) there is an interaction between learning method and social intelligence in its influence on learning performancefor citizenship education; (3) students learning resulting collaborative, who have high social intelligence, are greater than problem solving; and (4) low social intelegence students, there was no difference learning results by collaborative or problem solving either.